Immanuel Wallerstein and the Problem of the World : System, Scale, Culture - Tanoukhi, Nirvana; Robbins, Bruce; Palumbo-Liu, David (Book collections on Project MUSE., 2011)
Leading cultural theorists consider the meaning and implications of world-scale humanist scholarship by engaging with Immanuel Wallerstein s world-systems analysis.